Nancy Fraser and Karl Polanyi. A Possible Dialogue - Brie, Michael (Karl Polanyi in Dialogue: A Socialist Thinker for our Times, 2017)
From the very beginning a misunderstanding has to be cleared up – the reduction of Polanyi’s work to that of a reformer who wants to counter the excesses of market radicalism with social protective measures and believes that the crisis of modern
Philosophy
Keywords: FRASER; Nancy; triple movement

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state

Chapter 7: Karl Polanyi - Rogerson, Kenneth S.; May, Christopher (Key Thinkers for the Information Society, 2002)
This article presents Karl Polanyi's analysis of the dynamic relationships between economy and society in the information age. Of the many concepts Karl Polanyi provides in his analysis of economic relations, three stand as carefully calculated assumptions about the relationship between society and economy: the embeddedness of information in society, the commoditization of information and the existence of a double movement in the information revolution. Information has always been embedded in societal interactions. To emphasize this point, he said that the simple flow of information seems to have little effect in and of itself on the outcome of social interchanges. In Polanyi's words, it is also embedded in other social relations, such as political, economic, cultural, or health-related discussions and actions. On the issue of information commoditization, Polanyi takes a different view. His logic indicates that there will be negative social consequences associated with it. One example is digital divide or the discrepancies on a global or national level between those who have access to information through new technologies and those who do not. With regards to the existence of double movement, Polanyi believed that there are two opposing forces-economic liberalism and social protection-present during the industrial revolution. However, this is not easy to see in the information age because of simple paradox. First, people who would eschew the uses of technology for ideological reasons,may turn to it for other reasons. And second, there is only a protest of a specific issue and not the imbalance of information flows or the ownership of information dissemination methods.
Information Science; Philosophy; Communications
Keywords: commercialization; communication revolution; digital divide; industrial revolution; information technology; liberalism

Capitalism and Crisis: Thinking Through Capitalist Crisis with Schumpeter and Polanyi - Delanty, Gerard (Capitalism, Democracy, Socialism: Critical Debates, 2022)
The chapter offers an analysis of capitalist crisis through a reading and discussion of two seminal texts on capitalism, Joseph Schumpeter’s Capitalism, Socialism and Democracy [1943] and Karl Polanyi’s The Great Transformation [1944]. These inspiring works on economic history and social theory offer profound insights into the nature of capitalist crisis. Although written in the mid-twentieth century many of the insights in these books are of relevance to the current situation as capitalism undergoes another revulsion. While the two authors were very different – Polanyi a left-wing critic of capitalism; Schumpeter a politically right-wing economist who favoured capitalism – both were influenced by Marx’s analysis of capitalism and have helped to shape the debate on the crisis of capitalism. Indeed, Schumpeter was convinced Marx was mostly right in his prediction of the end of capitalism and the triumph of socialism. The chapter begins with a brief account of the Marxist theory capitalism in order to contextualise the discussion of the two theorists.
Political Science; Philosophy
Keywords: MARX; Karl; 1818-1883; Polanyi; SCHUMPETER; Joseph Alois; 1883-1950; capitalism; crisis